Subcellular trafficking of VHL and oxygen homeostasis: Discovery of a new nuclear export pathway - Khacho, Mireille (University of Ottawa (Canada), 2009)
Degradation of nuclear proteins by the ubiquitylation system often requires nuclear-cytoplasmic trafficking of E3 ubiquitin-ligases. The von Hippel-Lindau (VHL) tumor suppressor protein is the substrate recognition component of a Cullin-2-containing E3 ubiquitin-ligase that recruits the hypoxia-inducible factor (HIF) for oxygen-dependent degradation. The dynamic properties of VHL are essential for its ability to mediate efficient degradation of HIF. Interestingly, nuclear export of VHL requires ongoing transcription and is independent of the classical NES/CRM1 pathway. Examining this uncharacterized nuclear export pathway led to the identification of a discreet motif, "DxGx2Dx 2L", that directs transcription-dependent nuclear export of VHL. The "DxGx2Dx2L" motif is also found in other proteins, including Poly(A) Binding Protein (PABP1) to direct transcription-dependent nuclear export. The DxGx2Dx2L motif is denoted as TD-NEM (Transcription-Dependent Nuclear Export Motif) since inhibition of transcription by ActD or DRB abrogates its nuclear export activity. In VHL, TD-NEM is targeted by naturally-occurring mutations associated with renal carcinoma and polycythemia in humans. Disease-causing mutations of key residues of TD-NEM restrain the ability of VHL to efficiently mediate oxygen-dependent degradation of HIF by altering its nuclear export dynamics without affecting interaction with its substrate or core components of the E3 ubiquitin-ligase complex. Further studies aimed at understanding the mechanism of TD-NEM-mediated nuclear export led to the identification of a novel VHL and PABP1 interacting protein, the cytoplasmic translation elongation factor eEF1A. eEF1A, which has been implicated in the nuclear export of RNA species in lower eukaryotes, is involved in nuclear export of proteins encoding a TD-NEM in mammalian cells. eEF1A interacts specifically with TD-NEM and disrupting this interaction, by point mutations of the key residues within TD-NEM or siRNA-mediated knockdown of eEF1A, suppresses nuclear export. ActD suppresses eEF1A/TD-NEM interaction and abrogates eEF1A-mediated nuclear export of TD-NEM, providing a possible explanation for the inhibitory effect of ActD on nuclear export of TD-NEM-containing proteins. These results identify a novel and potentially ubiquitous, nuclear export motif, further highlight the role of nuclear-cytoplasmic shuttling of E3 ubiquitin-ligases in degradation of nuclear substrates and provide evidence that disease-causing mutations can target subcellular trafficking. Furthermore, these findings demonstrate that eEF1A, a mediator of RNA export in yeast, has an additional role in the nuclear export of proteins in mammalian cells.
Keywords: Biology, Molecular.; Biology, Cell.